Desfiando o bordado narrativo de Autran Dourado: um exercício de leitura do texto literário - Ramos, Angélica Maria de Almeida Carvalho (2019)
The research has as its main objective to investigate how time, coupled with mnemonic practices and the exercise of the imagination, is built on the novel O risco do bordado, by Waldomiro Autran Dourado (1926-2012), based on narrative strategies mobilized for its composition. Autran Dourado began his literary career in 1944, with the publication of the novel Teia, by the Building Editions, a work which follows Shadow and Exile and Time to Love (1952). The aesthetic project of the Minas Gerais writer is characterized, above all, by an intense dialogue with tradition, and with the literary and philosophical expressions that mark the history of Western civilization. Drinking from the source of the classics, the author builds his fiction using do-it-yourself, clippings, emulations of Greek tragedies, sketching the profile of his characters from a reconfiguration of myths, symbols and fables constitutive of the imagery of modern man. The time, in this sense, emerges as the spiral time of the myths in which one image refers to another, or rather, it lives within another, and can be resurrected at any moment by evocation or remembrance. Anguish, despair, and eroticism torn by guilt are some of the recurring themes in autochronic fiction. In O risco do Bordado, they are catalysed by the imagination of the character João Fonseca Nogueira, a spokesman for the fictional town of Duas Pontes. The childhood emerged as a fruitful backdrop to literary creation, from which the playful universe of fiction was inaugurated. Throughout the pages of the novel, drawing from the figure of John, the profile of a writer in a frank process of maturing, who, disconcerted by the opacity of memory, finds in the daydream the raw material for the creation of his world of fables. The use of the technique of narrative in blocks, the presence of the disorientating person narrator of the reading, the baroque game of shadow and light stand out with aesthetic resources. The motivational question of this research is therefore: how does the act of narrating, linked to mnemonic resources and the creative use of imagination, inaugurate new temporalities in the literary text? In order to try to problematize the question raised, this work is divided into three stages. First, the novel will be analyzed by weaving a discussion about the characteristics related to the romanesque structure, observing the aesthetic strategies already mentioned in this text, undertaken by the author to create the temporal coordinate of his narrative, and then to destroy it by giving to the imagination that disorients the whole proposed chronology. In the next, a hermeneutic path will be traced, unfolding the analysis of time in two axes of signification: that of the character, immersed in his passionate horizon, immersed in reverie, whom we accompany, with whom we have intimately suffered the flow of events by reconstructing the universe from their point of view; and the narrator who, seeing the events behind, tries to give a meaning to them from the memory effort. As a theoretical basis, the contributions of POUILLON (1974), MENDILOW(1972), BORNEUF(1971), STANZEL (1971), BAKHTIN (2008), ELIADE (1972), ISER (2002), AGOSTINHO (2008), BACHELARD (2009), MERLEAU-PONTY (1999), RICOEUR (2000), among others.